Semiconductive Copper(I)–Organic Frameworks for Efficient Light‐Driven Hydrogen Generation Without Additional Photosensitizers and Cocatalysts - Shi, Dongying; Zheng, Rui; Sun, Ming‐Jun; Cao, Xinrui; Sun, Chun‐Xiao; Cui, Chao‐Jie; Liu, Chun‐Sen; Zhao, Junwei; Du, Miao (Angewandte Chemie International Edition, 2017)
As the first example of a photocatalytic system for splitting water without additional cocatalysts and photosensitizers, the comparatively cost‐effective Cu2I2‐based MOF, Cu‐I‐bpy (bpy=4,4′‐bipyridine) exhibited highly efficient photocatalytic hydrogen production (7.09 mmol g−1 h−1). Density functional theory (DFT) calculations established the electronic structures of Cu‐I‐bpy with a narrow band gap of 2.05 eV, indicating its semiconductive behavior, which is consistent with the experimental value of 2.00 eV. The proposed mechanism demonstrates that Cu2I2 clusters of Cu‐I‐bpy serve as photoelectron generators to accelerate the copper(I) hydride interaction, providing redox reaction sites for hydrogen evolution. The highly stable cocatalyst‐free and self‐sensitized Cu‐I‐bpy provides new insights into the future design of cost‐effective d10‐based MOFs for highly efficient and long‐term solar fuels production. No additives required: A low‐cost Cu2I2‐based MOF exhibits efficient photocatalytic H2 production without additional photosensitizers and cocatalysts. DFT calculations reveal a good band alignment with the water redox energy levels. The proposed mechanism demonstrates that Cu2I2 clusters in Cu‐I‐bpy (bpy=4,4′‐bipyridine) serve as photoelectron generators to accelerate copper(I) hydride interaction for hydrogen evolution.